Analysis of Community Tradition and Knowledge with Covid-19 Prevention Efforts - Ganda Sigalingging; Zulkarnain Nasution; Magdalena Ginting; Poniyah Simanullang; Yemima (International Journal of Science and Society, 2021)
The application of health protocols to prevent the transmission of covid 19 is still relatively low, as is the case in Kabil Village, Batam City, which is still far from expected. Many factors can influence it, including the socio-cultural community, in this case, the inherent traditions/customs. The aim is to analyze the socio-cultural relationship with efforts to prevent Covid-19 in Kabil Village, Batam City. This research is a descriptive correlation with a cross-sectional approach involving 90 respondents, namely the people of Kabil Village in RW 015 and RW 016. The sampling technique is done by simple random sampling. Data were collected by interview using a questionnaire—data analysis using Chi Square test at 95% confidence level. A socio-cultural society based on tradition is more supportive; 53 respondents (58.9%) do not do prevention, as many as 37 respondents (41.1%). Statistical test results show that there is a relationship between tradition and efforts to prevent Covid-19 with a p-value of 0.012 (α < 0.05), good knowledge 37 people (41.1%) made prevention efforts as many as 22 people (24.3%). The statistical test results show a significant relationship between tradition/habits and knowledge with measures to prevent COVID-19 in Kabil Village, Batam City, with a p-value of 0.012 and knowledge with a p-value of 0.002.